Date Palm Seed Oil (Phoenix dactylifera L.) Green Extraction: Physicochemical Properties, Antioxidant Activities, and Phenolic and Fatty Acid Profiles - Hammadi Hamza; Walid Elfalleh; Kameleddine Nagaz (Journal of Food Quality)
Date palm seed oil is among the precious vegetable oils with low yield, whose extraction is commonly done with organic solvents which cause serious problems. This study aims to assess the effectiveness of orange peel essential oil as biosolvent for date seed oil extraction. Green extraction was conducted by Soxhlet apparatus as well as by soaking and compared with the Soxhlet method using petroleum ether. The GC-MS analysis of orange peel essential oil confirmed its richness with limonene (94.31%), which justifies its usefulness as green solvent. The latter gave higher yields, the extracted bio-oil was light brown with pleasant odor, and the characteristics were consistent with international standards. Based on the GC profiles, obtained oils were similar using both solvents, and the major compounds were oleic and lauric acids. The bio-oil phenolic content and the antioxidant activity were high, and the major compounds were the protocatechuic, chlorogenic, and 4-O-caffeoylquinic acids. Gallic and p-coumaric acids were the major compounds for oil extracted by petroleum ether.